Prevalence and risk factors of anxiety and depression in patients with multi-drug/rifampicin-resistant tuberculosis - Dan-ni, Zhang; Guang-min, Zheng; Yu-hua, Du; Ying, Lin; Ting, Wang; Yuan-yuan, Chen; Yu-hong, Xie; Xin-cai, Xiao (Frontiers in Public Health, 2024)
Background Mental health disorders in patients with multi-drug or rifampicin-resistant tuberculosis (MDR/RR-TB) receive consistent attention. Anxiety and depression can manifest and may impact disease progression in patients with MDR/RR-TB. Given the heightened stressors resulting from the COVID-19 pandemic, this scenario is even more concerning. Objective To evaluate the prevalence of and risk factors associated with anxiety and depression among patients with MDR/RR-TB in southern China. Methods A facility-based cross-sectional study was undertaken at Guangzhou Chest Hospital in southern China, encompassing a cohort of 219 patients undergoing outpatient and inpatient treatment for MDR/RR-TB. Anxiety and depressive symptoms were assessed using the 7-Item Generalized Anxiety Disorder (GAD-7) scale and Patient Health Questionnaire-9 (PHQ-9). The ramifications of anxiety and depression were examined using univariate and multivariate logistic regression analyses, with odds ratios (ORs) and age- and sex-adjusted ORs (AORs) employed to quantify their influence. All data underwent statistical analysis using SPSS 25.0, with statistical significance established at P < 0.05. Results Two hundred and nineteen individuals with MDR/RR-TB were included in the study. The prevalence of anxiety and depression was 57.53% (n = 126) and 65.75% (n = 144), respectively, with 33.3% (n = 73) of the participants experiencing both conditions simultaneously. Multivariate logistic regression analysis revealed that an age of 20–40 years [anxiety AOR = 3.021, 95% confidence interval (CI): 1.240–7.360; depression AOR = 3.538, 95% CI: 1.219–10.268], disease stigma (anxiety AOR = 10.613, 95% CI: 2.966–37.975; depression AOR = 4.514, 95% CI: 2.051–10.108) and poor physical health (anxiety AOR = 7.636, 95% CI: 2.938–19.844; depression AOR = 6.190, 95% CI: 2.468–15.529) were significant risk factors for moderate levels of anxiety and depression. Conclusions We found that individuals with MDR/RR-TB had an elevated risk of anxiety and depression. To decrease the likelihood of unfavorable treatment outcomes, it is imperative to carefully monitor the psychological wellbeing of patients with MDR/RR-TB and promptly address any detrimental psychiatric conditions.